Mobile banking: An analysis of usage in the present era - Arthi MC; Vinitha K (Global Business & Finance Review (GBFR), 2024)
Purpose: This article aims to study mobile banking usage in recent times and to understand the relationship between the perception of customers and actual usage trends. Design/methodology/approach: Primary data is collected using the survey method and various charts along with the TAM (Technology Acceptance Model) constructed using SmartPLS is used to understand the relationship. Findings: The results showcase a strong relationship between perceived ease of use, usefulness, intention to use, and actual usage of mobile banking. The findings demonstrate that mobile payments saw a surge in the present era, bank visits and chequebook usage dropped, and increased adoption in the older population. Research limitations/implications: The limitations that are observed in this research, are that it did not focus on some additional elements of mobile banking like mobile applications stability, customer care support, and security which can be analyzed using other models like UTAUT or IS system. Originality/value: The paper presents the patronage and usage of mobile banking in recent times after the pandemic and earlier demonetization in India. The analysis using the TAM model helped to check the current trend and users' mind-set shift.
Keywords: 650; Mobile banking; Perceived usefulness; Perceived ease of use; TAM; SmartPLS